Active seismic studies in valley glacier settings: strategies and limitations - JENNA M. ZECHMANN; ADAM D. BOOTH; MARTIN TRUFFER; ALESSIO GUSMEROLI; JASON M. AMUNDSON; CHRISTOPHER F. LARSEN (Journal of Glaciology, 2018)
Subglacial tills play an important role in glacier dynamics but are difficult to characterize in situ. Amplitude Variation with Angle (AVA) analysis of seismic reflection data can distinguish between stiff tills and deformable tills. However, AVA analysis in mountain glacier environments can be problematic: reflections can be obscured by Rayleigh wave energy scattered from crevasses, and complex basal topography can impede the location of reflection points in 2-D acquisitions. We use a forward model to produce challenging synthetic seismic records in order to test the efficacy of AVA in crevassed and geometrically complex environments. We find that we can distinguish subglacial till types in moderately crevassed environments, where ‘moderate’ depends on crevasse spacing and orientation. The forward model serves as a planning tool, as it can predict AVA success or failure based on characteristics of the study glacier. Applying lessons from the forward model, we perform AVA on a seismic dataset collected from Taku Glacier in Southeast Alaska in March 2016. Taku Glacier is a valley glacier thought to overlay thick sediment deposits. A near-offset polarity reversal confirms that the tills are deformable.